2020
DOI: 10.1002/mgg3.1573
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins syndrome: Clinical report and retrospective analysis of Chinese patients

Abstract: Background Treacher Collins syndrome‐1 (TCS1; OMIM# 154500) is a rare autosomal dominant disease that is defined by congenital craniofacial dysplasia. Here, we report four sporadic and one familial case of TCS1 in Chinese patients with clinical features presenting as hypoplasia of the zygomatic complex and mandible, downslanting palpebral fissures, coloboma of the lower eyelids, and conductive hearing loss. Materials and Methods Audiological, radiological, and physical examinations were performed. Targeted nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…Researchers analyzed TCS1 patients with TCOF1 variation in different populations, the results showed that exon 10, exon 15, exon 16, exon 23 and exon 24 were the hotspots of gene variation (Splendore et al, 2002). Pan et al (2021) showed that the hot spots of variants related to TCS1 in the Chinese population were located in exon 5, exon 23 and exon 24, which were different from the hot spot variants of TCOF1 gene in the two children in this study. According to the human genome mutation database (HGMD), more than 367 sites of variants have been reported in the TCOF1 gene.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Researchers analyzed TCS1 patients with TCOF1 variation in different populations, the results showed that exon 10, exon 15, exon 16, exon 23 and exon 24 were the hotspots of gene variation (Splendore et al, 2002). Pan et al (2021) showed that the hot spots of variants related to TCS1 in the Chinese population were located in exon 5, exon 23 and exon 24, which were different from the hot spot variants of TCOF1 gene in the two children in this study. According to the human genome mutation database (HGMD), more than 367 sites of variants have been reported in the TCOF1 gene.…”
Section: Discussionmentioning
confidence: 60%
“…TCS1 is a rare autosomal dominant disorder defined as congenital craniofacial dysplasia, characterized by unique “bird‐shaped” facial manifestations (malar and mandibular dysplasia, etc.) and conductive hearing loss (auricle, external auditory canal and middle ear malformations) (Pan et al., 2021 ). The main cause of TCS1 is the variants in TCOF1 locus, which is located on chromosome 5q32‐q33.1, containing 28 exons and encoding 4465 base pairs (Zhang et al., 2013 ); It also encodes a low‐complexity, and serine/alanine‐rich protein called the Treacle protein, which is composed of 1488 amino acids with a molecular weight of about 152 KD, and has three domains, namely the N‐terminal and C‐terminal, and a central repetitive domain (Pan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variant (NM_000356.3: c.4131_4135del, p.Lys1380Glufs*12) detected in sporadic patient T2220150810 was already known in previous reports. The variant (NM_000356.3: c.1535del, p.Pro512Leufs*7) was also a known one because patient T3720160105 was the same 1 as case 5 in the study of Pan et al (Pan et al, 2021). An SNP within POLR1D (NM_015972.3: c.139G>A, p.Glu47Lys) was detected in sporadic patient T1020160503 (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Of the 394 initial screened literature records, 334 records were excluded after reviewing the abstract, while 60 full articles were assessed for eligibility, 10 of them were excluded (due to no clinical features data), resulting in 43 TCOF1 1,2,8,13,17–55 and 10 POLR1 related studies 1,4,5,7,17,55–58 . Among them, there were three studies including both TCOF1 and POLR1D 1,17,55 .…”
Section: Resultsmentioning
confidence: 99%